Mapping the microbial diversity associated with different geochemical regimes in the shallow-water hydrothermal vents of the Aeolian archipelago, Italy - Barosa, Bernardo; Ferrillo, Alessandra; Selci, Matteo; Giardina, Marco; Bastianoni, Alessia; Correggia, Monica; di Iorio, Luciano; Bernardi, Giulia; Cascone, Martina; Capuozzo, Rosaria; Intoccia, Michele; Price, Roy; et al. (Frontiers in Microbiology, 2023)
Shallow-water hydrothermal vents are unique marine environments ubiquitous along the coast of volcanically active regions of the planet. In contrast to their deep-sea counterparts, primary production at shallow-water vents relies on both photoautotrophy and chemoautotrophy. Such processes are supported by a range of geochemical regimes driven by different geological settings. The Aeolian archipelago, located in the southern Tyrrhenian sea, is characterized by intense hydrothermal activity and harbors some of the best sampled shallow-water vents of the Mediterranean Sea. Despite this, the correlation between microbial diversity, geochemical regimes and geological settings of the different volcanic islands of the archipelago is largely unknown. Here, we report the microbial diversity associated with six distinct shallow-water hydrothermal vents of the Aeolian Islands using a combination of 16S rRNA amplicon sequencing along with physicochemical and geochemical measurements. Samples were collected from biofilms, fluids and sediments from shallow vents on the islands of Lipari, Panarea, Salina, and Vulcano. Two new shallow vent locations are described here for the first time. Our results show the presence of diverse microbial communities consistent in their composition with the local geochemical regimes. The shallow water vents of the Aeolian Islands harbor highly diverse microbial community and should be included in future conservation efforts.